How is environmental education addressed in Colombia? Between regulation and transformation: The case of the city of Tunja - Alejandra Uscategui-Gómez; Javier Molano-Malaver; Jonathan Igua-Muñoz (Journal of Environment and Sustainability Education, 2026)
This study evaluates the structure and level of development of School Environmental Projects (by their Spanish acronym, PRAE) in fourteen public institutions in the city of Tunja, Colombia. The aim was to determine whether these projects primarily operate as instruments of regulatory compliance or as educational initiatives oriented towards sustainable development. A documentary analysis was performed using an evaluative matrix comprising eight categories and 23 sub-categories. Development levels were estimated using a weighted qualitative scale, and multivariate and inferential analyses (principal component analysis -PCA and analysis of variance -ANOVA) were conducted to identify structural patterns and significant differences between categories. PCA explained 83.1% of the total variance of the collected information, confirming a structural dissociation between the conceptual formulation and operational implementation of the PRAEs. Additionally, statistically significant differences (p < 0.001) were demonstrated among the conceptual, pedagogical, projective, and intra-institutional categories. This indicates an urgent need to strengthen structured pedagogical aspects, applied research, and effective articulation with school governance. These findings have direct implications for public policy and school management in the field of environmental education in Colombia. Firstly, they emphasize the importance of transitioning from a regulatory approach to an institutionalised pedagogical model that incorporates PRAEs into the curriculum and school planning instruments. Secondly, there is an urgent need to strengthen teacher training in interdisciplinary approaches, research-based methodologies and situated learning to transform PRAEs into genuine learning territories.